A experiência da “Grande Guerra” nas páginas de Selecta (1914-1919) - Fagundes, Luciana Pessanha (Brasiliana: Journal for Brazilian Studies, 2021)
Abstract This article aims to analyze the magazine Selecta, published weekly from June 1915, in the city of Rio de Janeiro, between the years 1914 and 1919. The magazine aimed to complement the reading of another famous and popular weekly of the period: the magazine Fon-Fon! Quoted in countless studies, but never the target of a specific study, Selecta magazine presents some singularities that we perceive when analyzing it, focusing on its approach on a theme that is very important: the “Great War” (1914-1918). Thus, we intend to relate the series of changes in the scope of the magazine's format and content throughout its first four years of existence, with the central role that the Brazilian press acquired at that time, charged with reporting and representing the experience of war for Brazil.